COLORADO AGE-RELATED MACULAR DEGENERATION REGISTRY: Design and Clinical Risk Factors of the Cohort. Issue 4 (April 2019) - Lynch, Anne M.; Patnaik, Jennifer L.; Cathcart, Jennifer N.; Mathias, Marc T.; Siringo, Frank S.; Lacey Echalier, E.; Wagner, Brandie D.; Oliver, Scott C.N.; Pecen, Paula E.; Olson, Jeffrey L.; Fine, Stuart L.; Palestine, Alan G.; et al.
Abstract : Purpose: To study new and existing risk factors related to age-related macular degeneration (AMD) phenotypes in a Colorado cohort. Methods: Age-related macular degeneration was categorized into early, intermediate, or advanced forms. Controls (n = 180) were patients with cataract and no AMD. Demographic and clinical data were gathered by patient interview and verified by chart review. Image data were reviewed by vitreoretinal specialists. Statistical analysis included univariable and multivariate logistic regression analysis ( P < 0.05). Results: Among the 456 patients with AMD, 157 (34.4%), 80 (17.6%), and 219 (48.0%) had the early/intermediate, geographic atrophy, and neovascular forms of the disease, respectively. Adjusted for age, African-American race was associated with a reduced risk of early/intermediate (adjusted odds ratio [AOR] = 0.08, confidence interval [CI] = 0.01–0.67) and neovascular AMD (AOR = 0.15, CI = 0.03–0.72). A family history of AMD was a risk factor for early/intermediate (AOR = 4.08, CI = 2.30–7.25), geographic atrophy (AOR = 8.62, CI = 3.77–19.7), and neovascular AMD (AOR = 3.76, CI = 2.16–6.56). A history of asthma was related to the early/intermediate form of AMD (AOR = 2.34, CI = 1.22–4.46). Conclusion: Studying AMD in specific populations may reveal novel risk factors such as our finding of a relationship between asthma history and AMD. Abstract : Risk factors for age-related macular degeneration in a Colorado cohort.